Respuesta :

Answer:

y = -1, x = -1

Step-by-step explanation:

Because they are both equal to y, the equations can be rewritten as:

-2x - 3 = 3x + 2

You are now able to rearrange this equation to find the value of x.

-3 = 5x + 2       (Add 2x to each side)

-5 = 5x             (Subtract 2 from each side)

x = -1                (Divide both sides by 5)

Finally, you can substitute x back into the equation to work out the value of y:

y = -2(-1) - 3

y = 2 - 3

y = -1

You are now left with the results, y = -1 and x = -1.

Answer:

(-1,-1)

Step-by-step explanation:

-1 = -2(-1) - 3

-1 = 2 - 3

-1 = -1 TRUE

-1 = 3(-1) + 2

-1 = -3 + 2

-1 = -1 TRUE